Cereals and pulses - Brink, M.; Belay, G. (CTA / Backhuys Publishers / PROTA, 2006)
This book and CD-ROM describe cereals, pseudo-cereals and pulses, which are some of the 7,000 useful plants of tropical Africa. Of the 250 species listed as cereals, pseudo-cereals and pulses on PROTA’s database, 82 qualify for treatment in this volume through a series of review articles.